2018
DOI: 10.1111/sms.13036
|View full text |Cite
|
Sign up to set email alerts
|

Does the amount of lower extremity movement variability differ between injured and uninjured populations? A systematic review

Abstract: Movement variability during repetitive performance of a dynamic activity (eg, running, jumping, kicking) is considered an integral characteristic of optimal movement execution; however, its relationship with musculo-skeletal injury is not known. The primary aim of this study was to review published comparison trials to determine whether movement variability differs between uninjured controls and subjects with a lower limb musculo-skeletal injury. A systematic search of online databases; MEDLINE, Sports Discus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 59 publications
3
35
0
Order By: Relevance
“…The observation of a predominantly high level of weight-shifting freedom in the study group was consistent with the earlier hypothesis that variability in the human motor system is the pervasive "healthy norm" [26]. The adaptability and flexibility of a dynamic system are expressed as a multiplicity of modes of action [2], consequently, weight-shifting freedom appears to be a desired feature for gait efficiency. The purpose of the foot is to perform propulsion while maintaining balance; thus, the foot requires freedom of motion to adapt to various terrains.…”
Section: Discussionsupporting
confidence: 88%
“…The observation of a predominantly high level of weight-shifting freedom in the study group was consistent with the earlier hypothesis that variability in the human motor system is the pervasive "healthy norm" [26]. The adaptability and flexibility of a dynamic system are expressed as a multiplicity of modes of action [2], consequently, weight-shifting freedom appears to be a desired feature for gait efficiency. The purpose of the foot is to perform propulsion while maintaining balance; thus, the foot requires freedom of motion to adapt to various terrains.…”
Section: Discussionsupporting
confidence: 88%
“…Further, the manner in which the data driven framework approached the engineering feature was based on no input of expert knowledge (e.g. complexity [59], stiffness [60], variability [61]) or any advanced feature engineering techniques (principal component scores, non negative matrix factorisation or interactions between features). No additional engineering feature was used to keep the interpretable and meaningful for rehabilitation, while additional more complex features are likely to increase the reported classification accuracies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent theories have demonstrated that motor variability not only leverages equifinality, making the system more adaptable and stable to perturbation (i.e., overcoming varying terrain or recovering from a slip/trip) ( Cusumano and Dingwell, 2013 ; Dingwell et al, 2017 ), it also has other cost function benefits ( Gates and Dingwell, 2008 ). Specifically, by capitalizing on a larger workspace (greater relative variability) of movement patterns to perform steady-state (constant locomotion velocity) behaviors, energy can be dispersed through more supportive, anatomical structures, whereas limited motor variability (lower relative variability) may lead to site-specific mechanical overloading (cumulative mechanical stress) that can result in musculoskeletal injury (MSI) ( Baida et al, 2018 ; Nordin and Dufek, 2019 ). Likewise, motor variability can distribute positive mechanical workloads across a greater number of muscle fibers improving metabolic efficiency by reducing the fatigue of a specific subset of muscle fibers ( Gates and Dingwell, 2008 ).…”
Section: Introductionmentioning
confidence: 99%